Determination and Comparison of Different Photovoltaic Module Temperature Models for Kuching, Sarawak - Jakhrani, A.Q.; Othman, A.K; Rigit, A.R.H.; Samo, S.R. (IEEE, 2011)
This paper presents the approach of the different models that used to predict the module temperature, which is one of the most important factors responsible for lowering the performance of PV modules. The suitability of the models for PV module temperature prediction was examined in order to assess the anticipated behavior of module temperature increase with respect to ambient temperature and solar radiation. A total of 16 models has been selected and investigated by employing the monthly mean daily meteorological data of Kuching, Sarawak. It is revealed that most models exposed analogous tendency of module temperature and solar radiation intensity. However, their magnitude was quite dissimilar under constant solar radiation and ambient temperature conditions. This variation may be due to the use of different variables, climatic conditions, configuration of PV modules and approach used by various researchers.